(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
The constant struggle by the local authorities in addressing the waste problem would call for a thorough examination of the economics of waste management, as well as the need to search for the most appropriate enviro-economic policy instrument that can be employed in the context of a fast-paced developing economy such as Malaysia. A number of instruments have been put into practice by various authorities in Malaysia in particular, and in other countries in general, but the effectiveness of each is being questioned. It is hereby proposed that a new instrument be introduced in Malaysia, which is a variation of the “Polluters-Pay” Principle, as outlined in the 9th Malaysia Plan (2006-2010). The primary target ought to be the consumers, and not necessarily the producers: those who participate in a recycling scheme are not required to pay a certain levy when purchasing new goods. In return, when they deposit the unwanted items into recycling bins designated for different types of materials, they will be rewarded with equivalent credit points that can be redeemed at points of sale. It is anticipated in at least 7 aspects if a positive impact of the application of the proposed instrument would be realized. Thus, the waste recycling industry, as envisaged since the 8th Malaysia Plan (2001-2005), would become a reality.